Optimalisasi Integrasi Pertanian Dan Perikanan Dalam Mendukung Ketahanan Pangan Dan Pembangunan Pertanian Berkelanjutan - Maria Dela Telaumbanua; Dermawan Zebua (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
Food security is a strategic issue that continues to be a major concern in national development, particularly in developing countries with a high dependence on the agriculture and fisheries sectors. However, challenges such as limited land, environmental degradation, climate change, and low production efficiency remain major obstacles to the development of these two sectors. One approach considered capable of addressing these challenges is the integration of agricultural and fisheries systems. This study aims to examine the role and potential of agricultural and fisheries integration in increasing productivity, resource utilization efficiency, and food system sustainability. The research method used is a descriptive study with qualitative and quantitative approaches through field observations, interviews, and literature review. Research results show that an integrated agriculture and fisheries system can increase production yields, reduce operational costs, and positively impact the environment and farmers’ incomes. Therefore, the integration of agriculture and fisheries has the potential to become an adaptive and inclusive strategy for sustainable agricultural development.